Practices of Good Governance in Budhanilkantha Municipality: Local Government Initiatives - Khila Nath Sapkota (MASI Mandiri Edukasi, 2025)
This article explores good governance practices and public service delivery by elected representatives and administrative staff in Budhanilkantha Municipality, Nepal. It examines local government initiatives and emphasizes key principles of good governance such as accountability, transparency, justice, and participation. This study employs a mixed-methods approach, incorporating surveys and interviews, to assess key governance indicators, including transparency, accountability, public participation, and service delivery. Likewise, a stratified sampling method was used to select 120 respondents from all wards of Budhanilkantha Municipality. The findings provide a comprehensive overview of governance practices in the Municipality, highlighting strengths and improvement areas. While awareness of governance principles is generally high, challenges such as limited public participation, delayed public service delivery, and varying levels of transparency persist. The research underscores the importance of citizen engagement and the proactive implementation of good governance mechanisms to foster trust, enhance service delivery, and support sustainable local development. The insights derived from this case study offer valuable guidance for policymakers, practitioners, and community stakeholders seeking to strengthen governance frameworks at the local level.